Keep Your Eyes on Development: The Behavioral and Neurophysiological Development of Visual Mechanisms Underlying Form Processing - Van Den Boomen, Carlijn; van der Smagt, Maarten J.; Kemner, Chantal (Frontiers in Psychiatry, 2012)
Visual form perception is essential for correct interpretation of, and interaction with, our environment. Form perception depends on visual acuity and processing of specific form characteristics, such as luminance contrast, spatial frequency, colour, orientation, depth and even motion information. As other cognitive processes, form perception matures with age. This paper aims at providing a concise overview of our current understanding of the typical development, from birth to adulthood, of form-characteristic processing, as measured both behaviourally and neurophysiologically. Two main conclusions can be drawn. First, the current literature conveys that for most reviewed characteristics a developmental pattern is apparent. These trajectories are discussed in relation to the organisation of the visual system. The second conclusion is that significant gaps in the literature exist for several age-ranges. To complete our understanding of the typical and, by consequence, atypical development of visual mechanisms underlying form processing, future research should uncover these missing segments.